The role of exclusive breastfeeding in prevention of childhood epilepsy - Alexander Kurniadi; Elisabeth Siti Herini; Wahyu Damayanti (Paediatrica Indonesiana, 2015)
Background Epilepsy affects 1% of children worldwide. The highest incidence is in the first year of life, and perinatal factors, such as hypoxic-ischemic injury, infection, and cortical malformation may play etiologic roles. Breast milk contains optimal nutrients for human brain in early life. Breastfeeding has been associated with lower risk of infections, better cognitive and psychomotor development. However, the role of breastfeeding in preventing childhood epilepsy remains unclear. Objective To evaluate an association between exclusive breastfeeding and childhood epilepsy. Methods A case-control study conducted from 1 May to 3 July 2013 involving children with epilepsy aged 6 months to 18 years who were attending pediatric outpatient clinic of Dr. Sardjito Hospital, Yogyakarta. Neurologically normal children, individually matched by age and sex, visiting the same clinic were considered as controls. Exclusion criteria were children with structural brain abnormality, history of epilepsy in family, and who had history of neonatal seizure, intracranial infection, febrile seizure, and head trauma before onset of epilepsy. History of breastfeeding was obtained by interviewing the parents. The difference of exclusively breastfeeding proportion between cases and controls was analyzed by McNemar test. Results The total number of participants was 68 cases and controls each. Subjects with epilepsy had lower proportion of exclusively breastfed (48.5%) compared with controls (54.4%), but the difference was not statistically significant (P=0.541). Exclusively breastfeeding showed no statistical significance in decreasing risk of epilepsy (OR=0.71; 95%CI 0.32 to 1.61). Conclusions Exclusive breastfeeding for 4-6 months has no effect against childhood epilepsy.